2018
DOI: 10.1016/j.dib.2018.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Data on items of AKUSSI in Alkaptonuria collected over three years from the United Kingdom National Alkaptonuria Centre and the impact of nitisinone

Abstract: Alkaptonuria is a rare genetic disorder characterized by a high level of circulating (and urine) homogentisic acid (HGA), which contributes to ochronosis when it is deposited in connective tissue as a pigmented polymer. In an observational study carried out by National AKU Centre (NAC) in Liverpool, a total of thirty-nine AKU patients attended yearly visits in varying numbers. At each visit a mixture of clinical, joint and spinal assessments were carried out and the results calculated to yield an AKUSSI (Alkap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 1 publication
0
33
0
Order By: Relevance
“…This could at least partly be explained as the aim in TT1 is to have no activity of 4HPPD at all, while this is different in AKU. Although this low dose of NTBC initially failed to show a response on non-biochemical outcomes [60], a decrease in clinical progression of eye and ear ochronosis in AKU patients has recently been reported [62, 63]. It is not known whether long-term NTBC treatment in AKU is effective, neither is it known whether NTBC could prevent the severe bone disease caused by ochronosis in AKU patients if started early.…”
Section: Ntbc Treatment In Other Disorders Of Tyrosine Metabolismmentioning
confidence: 99%
“…This could at least partly be explained as the aim in TT1 is to have no activity of 4HPPD at all, while this is different in AKU. Although this low dose of NTBC initially failed to show a response on non-biochemical outcomes [60], a decrease in clinical progression of eye and ear ochronosis in AKU patients has recently been reported [62, 63]. It is not known whether long-term NTBC treatment in AKU is effective, neither is it known whether NTBC could prevent the severe bone disease caused by ochronosis in AKU patients if started early.…”
Section: Ntbc Treatment In Other Disorders Of Tyrosine Metabolismmentioning
confidence: 99%
“…Nitisinone therapy in the NAC, and in the NIH, decreased serum and urine HGA by over 95%, offering for all practical purposes a "biochemical" cure of AKU. [19][20][21][22] The aim of the study discussed further in this manuscript was to examine the effect of nitisinone on the ochronotic process in photographs of the eyes and ears, as well as in ear cartilage biopsies taken four years apart, in patients attending the NAC.…”
Section: Introductionmentioning
confidence: 99%
“…As AKU research has gathered traction and more patients have become involved in research, the AKUSSI has clearly demonstrated the effect of nitisinone on the various parameters of the index. It shows how effective the therapy is, adding further validation to its use in AKU, it reduces HGA but also demonstrates numerous secondary important features of monitoring patients and their tissues which become symptomatic during the course of the disease [77,78]. The efficacy of nitisinone is clearer seen in longitudinal studies spanning 3 years examining multiple patients with AKU, not only reducing HGA, but also arresting ocular and auricular ochronosis [59].…”
Section: Effectiveness Of Nitisinone In Akumentioning
confidence: 91%